2015
DOI: 10.1186/s12915-015-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Lhx8 regulates primordial follicle activation and postnatal folliculogenesis

Abstract: BackgroundThe early stages of ovarian follicle formation—beginning with the breakdown of germ cell cysts and continuing with the formation of primordial follicles and transition to primary and secondary follicles—are critical in determining reproductive life span and fertility. Previously, we discovered that global knockouts of germ cell-specific transcriptional co-regulators Sohlh1, Sohlh2, Lhx8, and Nobox, cause rapid oocyte loss and ovarian failure. Also factors such as Nobox and Sohlh1 are associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 51 publications
(73 reference statements)
5
57
0
Order By: Relevance
“…Many oocytes began to grow shortly after birth, accompanied by an increase in phosphorylated protein kinase B (AKT), indicating that PI3-kinase signaling was active and that FOXO3A translocated from the nucleus to the cytoplasm. Strikingly, however, the granulosa cells failed to undergo the squamous-cuboidal transition and the oocytes did not grow beyond~30 μm in diameter (Ren et al 2015). These results not only suggest that that LHX8 normally acts to maintain oocytes in a quiescent nongrowing condition, but may hint that signaling pathways that can relay the growth signal from the oocyte to the granulosa are dependent on LHX8.…”
Section: Initiation Of Oocyte Growthmentioning
confidence: 91%
See 1 more Smart Citation
“…Many oocytes began to grow shortly after birth, accompanied by an increase in phosphorylated protein kinase B (AKT), indicating that PI3-kinase signaling was active and that FOXO3A translocated from the nucleus to the cytoplasm. Strikingly, however, the granulosa cells failed to undergo the squamous-cuboidal transition and the oocytes did not grow beyond~30 μm in diameter (Ren et al 2015). These results not only suggest that that LHX8 normally acts to maintain oocytes in a quiescent nongrowing condition, but may hint that signaling pathways that can relay the growth signal from the oocyte to the granulosa are dependent on LHX8.…”
Section: Initiation Of Oocyte Growthmentioning
confidence: 91%
“…When Lhx8 was globally deleted, oocytes within primordial follicles failed to grow, suggesting an important role in oocyte growth (Choi et al 2008a;Pangas et al 2006). Recently, however, transgenic mice expressing Cre recombinase under the control of the promoter of Gdf9 were used to selectively inactivate Lhx8 in oocytes within primordial follicles (Ren et al 2015). Many oocytes began to grow shortly after birth, accompanied by an increase in phosphorylated protein kinase B (AKT), indicating that PI3-kinase signaling was active and that FOXO3A translocated from the nucleus to the cytoplasm.…”
Section: Initiation Of Oocyte Growthmentioning
confidence: 98%
“…This is indeed consistent with what we observed in the present study, i.e., early loss of oocytes at the primordial follicle stage when Lhx8 is ablated. Interestingly, a recent study showed that conditional ablation of Lhx8 at the primordial follicle stage led to oocyte loss in primordial follicles, whereas knockout of Lhx8 in oocytes of primary follicles resulted in the death of primary follicles [59], suggesting that oocyte loss is likely to occur at the follicular stage when Lhx8 is knocked out. This is also consistent with our hypothesis that LHX8 might be required to maintain the integrity of DNA in the oocytes, because repair of DNA breaks induced during prophase I continues until meiosis I has been completed-a process that begins with the resumption of meiosis at puberty [47].…”
Section: Dna Damage and Autophagymentioning
confidence: 99%
“…Ren et al (44) investigated the role of oocyte-specific pathways during primordial follicle activation. Their studies suggest that Lhx8 plays a crucial role in the differentiation of primary follicles and that a deficiency in LHX8 (-/-) causes infertility.…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 99%
“…The next stage begins primordial follicle activation. During this process, oocytes grow and the shape of the granulosa cells changes from flat to cuboidal in structure (44).…”
Section: Artykuł Przeglądowy Reviewmentioning
confidence: 99%